Synthetic stimuli-responsive 'smart' fibers. (June 2016) - Bou, Simon; Ellis, Amanda V; Ebara, Mitsuhiro
Graphical abstract: Highlights: Smart nanofibers for cancer therapy. Cell capture and release using switchable on/off smart fibers. Electrospinning fibers for tissue engineering. Fibers play an important role in biomedical applications and therefore it is important to develop a better understanding of the impact that fiber structure and morphology has on its function within these systems. This review examines synthetic stimuli-responsive smart fibers, the many methods used to prepare smart fibers and also the wide range of applications that continue to grow as this emerging field develops. It then summarizes some of the future directions this field is moving into.